2014
DOI: 10.1097/scs.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Computed Tomography–Guided Percutaneous Radiofrequency Thermocoagulation for Classic Trigeminal Neuralgia Patients Older Than 70 Years

Abstract: The incidence of trigeminal neuralgia (TN) in elderly patients is higher. However, for those with poor fitness, the optimal surgical treatment for those refractory to medical treatment is controversial. The aim of current study was to investigate the long-term outcome of computed tomography (CT)-guided percutaneous radiofrequency thermocoagulation (PRT) for 304 TN patients 70 years or older. We conducted a retrospective study of 304 elderly patients with TN who were treated with CT-guided PRT between 2002 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 21 publications
1
44
0
Order By: Relevance
“…The efficacy of RFT at both temperatures is coincident to that in previous studies [2830] and even better than that reported in several other studies. [21,31,32] Improved efficacy for pain relief in the current study might be associated with the following factors: as opposed to previous reports [4,14,22,33] that have investigated ITN and STN together, we strictly included ITN and excluded STN; we included V2, V3, and V2+V3 for RFT comparison but excluded V1 and V1 TN because RFT at a lower temperature, nerve block, or pulse RFT (PRFT) is required for V1, and thus V1 and V1 TN should be addressed separately. However, V1, V2, and V3 have been investigated together in many studies; RFT parameters were also influential.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of RFT at both temperatures is coincident to that in previous studies [2830] and even better than that reported in several other studies. [21,31,32] Improved efficacy for pain relief in the current study might be associated with the following factors: as opposed to previous reports [4,14,22,33] that have investigated ITN and STN together, we strictly included ITN and excluded STN; we included V2, V3, and V2+V3 for RFT comparison but excluded V1 and V1 TN because RFT at a lower temperature, nerve block, or pulse RFT (PRFT) is required for V1, and thus V1 and V1 TN should be addressed separately. However, V1, V2, and V3 have been investigated together in many studies; RFT parameters were also influential.…”
Section: Discussionmentioning
confidence: 99%
“…Facial numbness classification (grade I to IV) was recorded before the second MRI scanning. [2] If any patient got pain recurrence or did not receive pain relief during the following 6 months after the PRT procedure, the VAS would also be recorded. The Research Ethics Committee of Xuanwu Hospital approved this study and written informed consent was obtained from each participant.…”
Section: Methodsmentioning
confidence: 99%
“…[2,14] The puncture of gasserian ganglion was according to the Hartel anterior route. The best puncture approach to the oval foreman and the corresponding skin insertion point was determined by CT scanning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with typical TN usually respond to RF ablation [7][8][9][10][11][12][13]. Yet, limited studies have addressed the efficacy of RF in cases with atypical trigeminal neuralgia [14,15].…”
Section: Introductionmentioning
confidence: 99%